Voltage-controlled floating resistor using differential difference amplifier - Kumngern, Montree (My University, 2011)
This paper presents a new configuration to realize the voltage-controlled floating resistor, which is suitable for integrated circuit implementation. The proposed resistor is composed of MOS transistor operating in the non-saturation region, differential difference amplifier (DDA) and MOS voltage divider. The MOS transistor operating in the non-saturation region is used to configure a floating linear resistor. The DDA and the MOS transistor voltage divider are used for canceling the nonlinear component term of MOS transistor in the non-saturation region to obtain a linear current/voltage relationship. The DDA is employed to provide a simple summer of the circuit. The resistor circuit also offers an ease for realizing the voltage divider circuit and the temperature effect that includes in term of threshold voltage can be compensated. The performances of the proposed circuit are simulated with PSPICE to confirm the presented theory. © 2011 IEEE.
Keywords: CMOS; differential difference amplifier (DDA); voltage-controlled floating resistor